Hidden in Plain Sight: Making Maine’s Science Leadership Visible - Dickerson, Kate (Maine Policy Review, 2018)
Kate Dickerson reports an innovative strategy to highlight Maine’s science leadership and to inspire both current and future generations of Maine’s science leaders by providing a space where they can talk about their work with the public: the Maine Science Festival, where attendees of all ages explore and celebrate the science happening in Maine.